Does Finance Access Matters for Children? An Evidence Form Indonesia Family Life Survey 5 and 4 - Riswanti Budi Sekaringsih (Global Review of Islamic Economics and Business, 2017)
As explained in the declaration of Sustainable Development Goals (SDG) in January 2016, two of the achievements are good health and wellbeing and quality education. Households as one of the drivers of the economy, household should be able to improve this achievement. Because There are two kinds of household’s outcome such as; child health and child education. One of the factors that influence this outcome is household financial access. A household who had better access on finance was more sustain than the other. This study aims to examine the impact of household financial acces on child education and child health. Source of data that used is Indonesia Family Life Survey (IFLS/SAKERTI) year 2014 and 2007. The recognition that finance access is an input in a household's production function has major implications for development. It suggests that the acquisition of human capital and the establishment of a physical infrastructure needs to be complemented by human investment the estimation is done in three ways; pooled OLS, fixed effect and random effect. The result shows that finance access matters for child health, specially the availability of BRI and BMT in village. And for child education, finance access specially the availability of BRI and BMT in village have positive impact for child education.